Effect of Presprouting Plant Growth Regulators and Natural Materials on Dormancy, Growth, and Yield of Potatoes (Solanum tuberosum L.) - M. S. Moletsane; P.K. Kimurto; M.E. Oyoo (Advances in Agriculture)
Irish potatoes are amongst the most highly grown and demanded crops in Kenya for food, industrial starch, and animal feed. Farmers, however, face a serious challenge regarding the timely availability of well-sprouted seed potato tubers due to the physiological seed dormancy period of 2–3 months, thereby reducing production cycles. This study determined the effects of different chitting methods on enhancing the presprouting of different potato varieties in Kenya. Plant growth regulators (PGR) (Gibberellins (GA3), 6-Benzylaminopurine, and Zeatin) and natural materials (grass, banana leaves, and soil) were evaluated for their effects in breaking dormancy and stimulating the growth of sprouts under greenhouse conditions in a complete randomized design (CRD) with three replicates. The evaluation of the presprouted seed in the field was conducted at Egerton University and Kenya Agricultural and Livestock Research Organization (KALRO), Molo, in a split-plot design for two seasons. Data was taken on crop emergence, length, thickness, and colour of sprouts, plant height, tubers per plant, tuber thickness, and tuber yield. Data were subjected to a general linear model to partition the variance component using SAS software version 9.13, and means were separated using the least significant difference (p≤0.05). There were significant (p≤0.05) main effects on the prespouting time, growth, and yield of tubers. The interaction effects due to variety and treatment were also significant (p≤0.05) for sprout thickness. Natural materials produced the most vigorous sprouts, increased crop emergence, plant height, and superior tuber yield. Natural materials and PGRs increased tuber size for chitted potato seed by 261% and 103%, respectively. Control treatments had a significantly higher frequency of small-sized tubers than natural materials and PGRs, proving the importance of chitting in increasing tuber size and yields. Natural materials increased sprout quality (thickness and length) better than PRGs and control treatments. This study showed that small-holder farmers could adopt the use of readily available soil, grass, and banana leaves while large-scale growers, with access to better facilities, could use PGRs to break tuber dormancy for increased potato tuber yield.